2014
DOI: 10.1097/pgp.0b013e3182936503
|View full text |Cite
|
Sign up to set email alerts
|

Verrucous Carcinoma of the Endometrium

Abstract: Verrucous carcinoma of the endometrium is an exceedingly rare disease with only a few cases reported in the literature. We describe the case of a 68-year-old postmenopausal patient who presented with vaginal discharge. PAP smears were repeatedly reported negative and an endometrial curettage 2 years prior to the diagnosis only showed fragments of benign squamous epithelium. Because of continuous symptoms a hysterectomy was performed and revealed extensive squamous metaplasia of the endometrium with focal trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…A total of 28 cases was identified in 14 studies (Table 4). 4,5,[7][8][9][10][11][12][13][14][15][16][17][18] The median age at diagnosis was 62 years, which is slightly younger than the women in our study (mean and median, 78 y). The majority of cases were negative for ER and PR in 19/23 (82.6%) and 19/22 (86.4%) cases, respectively.…”
Section: Fluhmann Criterion: a Simultaneous Cervical Scc Should Be Ab...mentioning
confidence: 85%
See 3 more Smart Citations
“…A total of 28 cases was identified in 14 studies (Table 4). 4,5,[7][8][9][10][11][12][13][14][15][16][17][18] The median age at diagnosis was 62 years, which is slightly younger than the women in our study (mean and median, 78 y). The majority of cases were negative for ER and PR in 19/23 (82.6%) and 19/22 (86.4%) cases, respectively.…”
Section: Fluhmann Criterion: a Simultaneous Cervical Scc Should Be Ab...mentioning
confidence: 85%
“…This is similar to the results of this study, where ER and PR were negative in all cases. An aberrant p53 expression pattern was identified in at least 4 of 21 (19%) reported cases 5,7–10,18. Before the recommendations for p53 immunohistochemical reporting in endometrial carcinomas were established,22,23 some reported HPV-independent PESCCs were described as p53 “positive” or “negative.” However, it is challenging to determine if cases reported as “positive” represent an aberrant/mutation-type pattern with diffuse nuclear overexpression, an aberrant cytoplasmic staining pattern, or a normal/wild-type pattern when the specific details of p53 immunostaining interpretation are not provided, as is the situation in 2 of 21 (10%) prior cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Auch diese Sonderfär-bungen zeigten einen weitgehend organoiden plattenepithelialen Aufbau ohne proliferierende oder p53-positive Zellen in den oberen oder mittleren Epithellagen. Da [3]. Zwar sind primä-re Plattenepithelkarzinome des Endometriums, die nicht mit plattenepithelial ausreifenden endometrioiden Adenokarzinomen verwechselt werden dürfen, in der WHO-Klassifikation beschrieben, aber es ist ein sehr seltenes Ereignis.…”
Section: Morphologischer Befundunclassified